2015
DOI: 10.1653/024.098.0243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nucleopolyhedrovirus Infection on the Development ofHelicoverpa armigera(Lepidoptera: Noctuidae) and Expression of Its 20-Hydroxyecdysone—and Juvenile Hormone—Related Genes

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…However, these data were not analyzed statistically because the numbers of survivors were few. Reductions in weight of pupae derived from larvae treated with their homologous nucleopolyhedrovirus compared with control pupae also were observed in S. exigua (Cabodevilla et al 2011b) and H. armigera (Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, these data were not analyzed statistically because the numbers of survivors were few. Reductions in weight of pupae derived from larvae treated with their homologous nucleopolyhedrovirus compared with control pupae also were observed in S. exigua (Cabodevilla et al 2011b) and H. armigera (Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, Cabodevilla et al (2011b) found that when second-instar S. exigua larvae were inoculated with 3.8 × 10 2 occlusion bodies per mL, the larval development time was about 2 d longer than that of healthy insects. When fourth-and fifth-instar H. armigera larvae were treated with different concentrations (1 × 10 6 to 1 × 10 10 occlusion bodies per mL) of its homologous nucleopolyhedrovirus (HaSNPV), the development time was longer significantly in most of the treated larvae (range: 16 to 32% and 17 to 27% for fourth and fifth instars, respectively) than in healthy insects (Zhang et al 2015). Additionally, in the occlusion body-production experiment of the present study, the weight of pupae derived from treated larvae (about 70 mg) was reduced by 30% relative to that of the control pupae (about 100 mg; data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain virus suspension, 0.02 g of HaSNPV raw powder (5 × 10 11 OBs/g) was diluted in sterile water to two different concentrations (10 8 and 10 6 OBs/ml; Zhang, Wu et al., ). Newly moulted fourth instars were inoculated with HaSNPV by feeding on a piece of artificial diet (0.8 cm L × 0.8 cm W × 0.5 cm H) contaminated with 10 μl of HaSNPV suspension at one of the two virus concentrations (i.e., a single larva ingested either 10 6 or 10 4 OBs).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, baculovirus infection altered the expression of host genes responsible for antivirus peptide production, detoxification, hormone activity and energy generation, among others using transcriptome analysis in baculovirus‐infected larvae (Breitenbach, Shelby, & Popham, ; Choi et al., ; Li et al., ). HaSNPV infection in H. armigera larvae led to down regulation of several 20E‐related genes and up regulation of JH‐related genes, indicating probable hormone mediation of climbing behaviour (Zhang, Wu et al., ). 20E and JH are the principal hormones that coordinately control growth and metamorphosis of holometabolous insects (Riddiford, Hiruma, Zhou, & Nelson, ).…”
Section: Introductionmentioning
confidence: 99%